Coupled versus uncoupled hindcast simulations of the Madden‐Julian Oscillation in the Year of Tropical Convection. Issue 15 (8th August 2014) - Shelly, Ann; Xavier, Prince; Copsey, Dan; Johns, Tim; Rodríguez, José M.; Milton, Sean; Klingaman, Nicholas
Abstract This study investigates the impact of a full interactive ocean on daily initialized 15 day hindcasts of the Madden‐Julian Oscillation (MJO), measured against a Met Office Unified Model atmosphere control simulation (atmospheric general circulation model (AGCM)) during a 3 month period of the Year of Tropical Convection. Results indicate that the coupled configuration (coupled general circulation model (CGCM)) extends MJO predictability over that of the AGCM, by up to 3–5 days. Propagation is improved in the CGCM, which we partly attribute to a more realistic phase relationship between sea surface temperature (SST) and convection. In addition, the CGCM demonstrates skill in representing downwelling oceanic Kelvin and Rossby waves which warm SSTs along their trajectory, with the potential to feedback on the atmosphere. These results imply that an ocean model capable of simulating internal ocean waves may be required to capture the full effect of air‐sea coupling for the MJO.